Rare site of presentation of a rare manifestation of graves’ disease (Indian Journal of Case Reports, 2018)
Infiltrative dermopathy is an uncommon manifestation of Graves’ disease frequently involving the lower extremities. The pretibial area is most commonly involved. Rarely the fingers, hands, elbows, arms, or face are affected. Skin thickening is the characteristic abnormality. Localized myxedema is an autoimmune manifestation of Graves’ disease. Here, we report the case of a 45-year-old who presented with thyroid-associated orbitopathy and localized myxoedema over both the shoulders. In a patient who has long-standing hyperthyroidism, the diagnosis of infiltrative dermopathy is usually confirmed by the location, non-pitting nature, and distinct borders of the lesions. As most of these lesions are asymptomatic, no specific therapy is required.